2021
DOI: 10.1136/bmjgast-2021-000765
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis identifies differences in the transcriptional targets of duodenal versus pancreatic neuroendocrine tumours

Abstract: ObjectiveGastroenteropancreatic neuroendocrine tumours (GEP-NETs) encompass a diverse group of neoplasms that vary in their secretory products and in their location within the gastrointestinal tract. Their prevalence in the USA is increasing among all adult age groups.AimTo identify the possible derivation of GEP-NETs using genome-wide analyses to distinguish small intestinal neuroendocrine tumours, specifically duodenal gastrinomas (DGASTs), from pancreatic neuroendocrine tumours.DesignWhole exome sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 56 publications
(48 reference statements)
3
40
0
Order By: Relevance
“…Previous work by our group demonstrated that non-cell autonomous loss of menin protein in enteric glial cells induces gastrin hormone expression [13,14] . Furthermore, human duodenal NETs are known to express glial cell markers, with some cells within the tumor exhibiting expression of both the neuroendocrine marker Syp and the glial-specific protein S100b [14,60] . We recently used digital spatial profiling to characterize neuroglial features in a small subset of human duodenal NETs [60] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work by our group demonstrated that non-cell autonomous loss of menin protein in enteric glial cells induces gastrin hormone expression [13,14] . Furthermore, human duodenal NETs are known to express glial cell markers, with some cells within the tumor exhibiting expression of both the neuroendocrine marker Syp and the glial-specific protein S100b [14,60] . We recently used digital spatial profiling to characterize neuroglial features in a small subset of human duodenal NETs [60] .…”
Section: Discussionmentioning
confidence: 99%
“…In identifying molecular features unique to the tumor-naïve hyperplastic antrum, we focused on a subset of genes enriched in our study and previously reported to be upregulated in human duodenal gastrinomas (DGASTs), including Hap1, Mn1 , and Uchl1 [60] . Among these, the neuronal protein Huntingtin-associated protein (Hap1) is also expressed by enteroendocrine cells (EECs) within the GI tract and was recently reported to be expressed in G cells but not in other EEC lineages of the pyloric antrum [61] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescent analysis indicated strong immunoreactivity of tumor cells, Brunner's glands, and the tumor stroma for both cytokines and downstream pSTAT3 activation. 149 Both IL-17 and TNF⍺ are known to activate downstream targets through NF-κB and pSTAT3 signaling pathways. Furthermore, previous studies have shown that STAT3 binds the SYP promoter, suggesting a direct mechanism for cytokine-induced neuroendocrine reprogramming.…”
Section: Molecular Heterogeneity Of Gep-netsmentioning
confidence: 99%
“… 150–152 In support of this, treatment of normal human duodenal organoids with TNF⍺ stimulated NF-κB and pSTAT3 activation and these events coincided with increased expression of neuroendocrine transcripts SYP, CHGA , and the gastrin-specification factor NKX6.3 . 149 , 153 , 154 Cytokine-mediated regulation of NKX6.3 is underscored by in silico analysis identifying an NF-κB binding site in the 5’ UTR of the NKX6.3 promoter. Taken together, these observations suggest a role for inflammatory cytokines in potential reprogramming of the Brunner's glands in favor of neuroendocrine differentiation and tumorigenesis ( Figure 2 ).…”
Section: Molecular Heterogeneity Of Gep-netsmentioning
confidence: 99%